AB195. SOH26AB_0227. The evolving face of fat necrosis in breast radiology—a pictorial review - Curran, Michael; Byrne, Mary; Lavelle, Marie; Brennan, Cressida; Barry, Josephine (Mesentery and Peritoneum, 2026)
Fat necrosis is a common entity which poses a significant diagnostic challenge to both clinicians and radiologists. It is a benign pathology that can present as a sequelae of trauma, surgery, or cosmetic procedures. Presenting symptoms and radiological findings depend on the stage of evolution. This pictorial review aims to highlight some of the diagnostic challenges related to the evolving appearance of fat necrosis and provide some practical tips to support safe and accurate radiological assessment.